EFFECT OF GLYCEROL CONCENTRATION VARIATIONS ON THE CHARACTERISTICS OF EDIBLE FILM MADE FROM KEPOK BANANA (Musa Paradisiaca) PEEL - Nur Nik Safika; Devi Tanggasari (Universitas Muhammadiyah Mataram, 2025)
The increasing accumulation of synthetic plastic waste has become a major environmental concern, necessitating the development of environmentally friendly packaging alternatives, such as edible films. This approach contributes to the advancement of sustainable food packaging while simultaneously enhancing the value of agro-industrial waste. Therefore, this study aimed to investigate the effect of different glycerol concentrations on the characteristics of edible films produced from kepok banana peels and agar. The parameters evaluated included moisture content, thickness, yield, and color. The experiment was conducted using a Completely Randomized Design (CRD) with three glycerol concentration treatments (0.5%, 1%, and 1.5%), each performed in triplicate. The results showed that glycerol addition significantly affected the moisture content, yield, and color of the Edible films, but had no significant effect on thickness. A glycerol concentration of 1% produced the best results, characterized by optimal moisture content and flexibility, high yield, and brighter color. This study demonstrates that the utilization of kepok banana peel waste in Edible film production has strong potential as an environmentally friendly alternative to conventional plastic packaging.